Some Behavioural and Physiological Effects of Plastics (Polyethylene) on Fish - Orose, Ekinadose; Wokeh, Okechukwu Kenneth; Okey-Wokeh, Chidinma Georginia (Tropical Aquatic and Soil Pollution, 2023)
Waste generation and disposal, particularly of plastics, have grown significantly over time due to the rapid expansion of urban development. Aquatic species are especially threatened by plastic pollution because the aquatic ecosystem serves as a sink for all contaminants. The capacity for regular development and reproduction is crucial for both human and wildlife health. The endocrine system, which comprises numerous glands that emit hormones to control blood sugar, growth, reproduction, metabolism, and the development of the brain, normally controls these functions. The majority of the synthetic organic chemicals used in plastics come from petroleum. It is well known that their effects cause the endocrine system's regular operation to be disrupted. Plastics are produced at a low cost, and their light weight and adaptability make them candidates for a wide range of uses in all facets of daily life. Plastic waste can enter the ecosystem through waste discharges from oil and gas platforms, aquaculture, and landfills, as well as through litter such as bags and plastic bits used as abrasives. Because they include indigestible particles that fill the stomach and lessen appetite, plastics have been implicated in harming the health of a variety of creatures. They were also discovered in the gastrointestinal tract of individual fish after one week, which disrupted the food's flow to the intestinal mucosa and had an impact on the fish's growth and physical condition. Additionally, fish exposed to plastics have been shown to exhibit changed behavior, decreased sperm motility, and increased thyroid hormone production. Therefore, exposure to varied amounts of polyethylene impairs an organism's normal physiological functioning and has the potential to impact negatively on both the health of the organism and its offspring. This review was aimed at highlighting the risks of plastic exposure to fish and people through the food chain.